Analog Waves, 2009 - Moren, Lisa (Lisa Moren, 2010)
This is the last hour of analog tv playing with an HD video of the atlantic ocean projected onto a 300lb block of ice. This documentation is day 2 of the installation when half of the ice is partially melted. © Lisa Moren, 2009
Keywords: Atlantic Ocean; Analog TV; Block of ice